2010
DOI: 10.1002/jobm.201000034
|View full text |Cite
|
Sign up to set email alerts
|

Surface hydrophobicity, nutritional contents affect Staphylococcus aureus biofilms and temperature influences its survival in preformed biofilms

Abstract: The present study investigates the effect of surface hydrophobicity and media on in vitro biofilm formation potential of S. aureus isolates from two dairies. There was lack of correlation between biofilm formation potential of S. aureus and sampling points but not with the source of isolation. Biofilm formation was more pronounced on hydrophobic polypropylene (PP) than hydrophilic stainless steel (SSC). A better correlation was established between the biofilms on SSC and PP when analyzed by crystal violet stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 44 publications
7
38
1
1
Order By: Relevance
“…Pagedar, Singh and Batish (2010) observed that S. aureus cells had higher capacity to form biofilms on polystyrene than stainless steel, suggesting that hydrophobicity was an important factor in the formation of the biofilms, which is in agreement with the differences in the PAA efficiency on polystyrene and stainless steel surfaces as observed in the present study. The survival of L. monocytogenes adhered cells after treatment with PAA at 0.5% (5,000 mg/L), which is nearly ten times over the concentrations normally used in food industries (300 -700 mg/L), indicate the magnitude of risk posed by a potential failure in cleaning and disinfection procedures, including the possibility of L. monocytogenes persistence in the food processing environment.…”
Section: Resultssupporting
confidence: 92%
“…Pagedar, Singh and Batish (2010) observed that S. aureus cells had higher capacity to form biofilms on polystyrene than stainless steel, suggesting that hydrophobicity was an important factor in the formation of the biofilms, which is in agreement with the differences in the PAA efficiency on polystyrene and stainless steel surfaces as observed in the present study. The survival of L. monocytogenes adhered cells after treatment with PAA at 0.5% (5,000 mg/L), which is nearly ten times over the concentrations normally used in food industries (300 -700 mg/L), indicate the magnitude of risk posed by a potential failure in cleaning and disinfection procedures, including the possibility of L. monocytogenes persistence in the food processing environment.…”
Section: Resultssupporting
confidence: 92%
“…Results on efficacy of biocide to control biofilms have been presented in Fig.1. These findings are in agreement with results of Pagedar et al, (2010), who also demonstrated that biofilms were most resistant to sodium hypochlorite and benzalkonium chloride and least to iodophore.…”
Section: Efficacy Evaluation Of Biocides On Biofilm Formationsupporting
confidence: 92%
“…Biofilms were grown in 96-well plates (European catalog number 734-2327; VWR, Radnor, PA;) with a total volume of 200 l of medium per well and a starting inoculum approximately equal to 10 7 CFU/ml (optical density at 620 nm [OD 620 ] of 0.005). Biofilm production is described as highly dependent on the temperature of the culture medium (20,21). Preliminary experiments showed that a strong biofilm was obtained at 30°C in Bacto tryptic soy broth (TSB; Becton, Dickinson, Franklin Lakes, NJ) supplemented with 0.25% glucose and 0.5% NaCl for the two strains investigated here.…”
Section: Methodsmentioning
confidence: 97%